PENGARUH PENGGUNAAN EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP PENURUNAN TINGKAT KECEMASAN PADA PASIEN - Dwi Septiningsih; Febi Ratnasari (Nusantara Hasana Journal, 2021)
Anxiety is a mental disorder that is often experienced by individuals, where this anxiety has an increasing prevalence each year. WHO estimates that by 2020, the leading causes of individual disability worldwide, namely anxiety and psychiatric disorders, account for around 15% of global morbidity. In Indonesia, based on Riskesdas in 2018, around 6.1% of Indonesia's population shows symptoms of mental and emotional disorders. Anxiety has a prevalence of 5%. There are several interventions that can be done to reduce anxiety levels, including Emotional Freedom Technique (EFT). This literature review aims to determine and analyze journal results related to the effect of Emotional Freedom Technique (EFT) on reducing anxiety in patients. The results of the analysis show that EFT is effective in reducing anxiety, stress of childbirth, depression in the elderly, affects the decrease in cortisol levels in the blood and can improve the quality of life. Search based on keywords from Emotional Freedom Technique (EFT) and access to databases such as PubMed, ScienceDirect, Elsevier. By using a prism chart, 20 related articles were obtained and a simple literature review method was carried out.